2012
DOI: 10.1021/ja302851n
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Exchange Coupling in 3d-Gd Complexes: Large Magnetocaloric Effect Systems

Abstract: Polynuclear 3d transition metal-Gd complexes are good candidates to present large magnetocaloric effect. This effect is favored by the presence of weak ferromagnetic exchange interactions that have been investigated using methods based on Density Functional Theory. The first part of the study is devoted to dinuclear complexes, focusing on the nature and mechanism of such exchange interactions. The presence of two bridging ligands is found more favorable for ferromagnetic coupling than a triple-bridged assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
96
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(101 citation statements)
references
References 80 publications
5
96
0
Order By: Relevance
“…The 6s orbitals, being spherical, cannot be solely responsible for FM exchange coupling, owing to symmetry. Thus, it is reasonable to conclude that the 5f orbitals must be involved, and this finding is in keeping with recent computational analysis of exchange coupling in related binuclear 3d metal-Gd III complexes [86]. M a n u s c r i p t Figure 14.…”
Section: Lanthanide Complexessupporting
confidence: 84%
“…The 6s orbitals, being spherical, cannot be solely responsible for FM exchange coupling, owing to symmetry. Thus, it is reasonable to conclude that the 5f orbitals must be involved, and this finding is in keeping with recent computational analysis of exchange coupling in related binuclear 3d metal-Gd III complexes [86]. M a n u s c r i p t Figure 14.…”
Section: Lanthanide Complexessupporting
confidence: 84%
“…7,8 From heat capacity measurements, we found that the magnetic entropy change reaches significant values for 1-3 K, namely DS m = 23.5 J kg À1 K À1 for DB = 7 T. Our results therefore suggest that the Gd…”
mentioning
confidence: 55%
“…Recently, a theoretical study of exchange coupling in 3d-Gd complexes appeared in the literature [34]. The authors demonstrate that the presence of the 5d Gd functions in their basis set is necessary to properly reproduce the experimental J values.…”
Section: Discussionmentioning
confidence: 99%